Microbiome of juvenile corals in the outer reef slope and lagoon of the South China Sea: insight into coral acclimatization to extreme thermal environments. (14th June 2021) - Qin, Zhenjun; Yu, Kefu; Chen, Shuchang; Chen, Biao; Liang, Jiayuan; Yao, Qiucui; Yu, Xiaopeng; Liao, Zhiheng; Deng, Chuanqi; Liang, Yanting
Summary: Environmental conditions between the outer reef slope (ORS) and lagoon in tropical atolls are significantly different, but the variations of juvenile coral‐microbiomes in the two environments and their relationship with coral thermal acclimatization are poorly understood. We explored this issue based on local water conditions and the microbiome of juvenile corals in the ORS and lagoon in the central South China Sea. Coral‐symbiotic Symbiodiniaceae showed significant differences among coral species; Pocillopora verrucosa and Pachyseris rugosa in the ORS, and Acropora formosa in the lagoon were dominated by Durusdinium, but other corals were dominated by Cladocopium . Although A. formosa in the ORS were dominated by Cladocopium (C3u), they were dominated by Durusdinium (D1/D1a) and Cladocopium (C50) in the lagoon. Other coral species were both dominated by Cladocopium in the lagoon and ORS. The relative abundance of bacteria in the Deinococcus–Thermus was generally higher in the lagoon corals than in the ORS corals. Our study indicates that P. verrucosa, P. rugosa and Porites lutea may have high thermal tolerance based on the relatively high abundance of heat‐tolerant Durusdinium and Thermus scotoductus . Likewise, A. formosa in the lagoon may acclimatize to the thermal environment based on a high relative abundance of heat‐tolerant Durusdinium .